Ogg1-Dependent DNA Repair Regulates NLRP3 Inflammasome and Prevents Atherosclerosis. Issue 6 (2nd September 2016) - Tumurkhuu, Gantsetseg; Shimada, Kenichi; Dagvadorj, Jargalsaikhan; Crother, Timothy R.; Zhang, Wenxuan; Luthringer, Daniel; Gottlieb, Roberta A.; Chen, Shuang; Arditi, Moshe
Abstract : Rationale: : Activation of NLRP3 (nucleotide-binding domain and leucine-rich repeat pyrin domain containing 3) inflammasome-mediating interleukin (IL)-1β secretion has emerged as an important component of inflammatory processes in atherosclerosis. Mitochondrial DNA (mtDNA) damage is detrimental in atherosclerosis, and mitochondria are central regulators of the nucleotide-binding domain and leucine-rich repeat pyrin domain containing 3 inflammasome. Human atherosclerotic plaques express increased mtDNA damage. The major DNA glycosylase, 8-oxoguanine glycosylase (OGG1), is responsible for removing the most abundant form of oxidative DNA damage. Objective: : To test the role of OGG1 in the development of atherosclerosis in mouse. Methods and Results: : We observed that Ogg1 expression decreases over time in atherosclerotic lesion macrophages of low-density lipoprotein receptor ( Ldlr ) knockout mice fed a Western diet. Ogg1 −/− Ldlr −/− mice fed a Western diet resulted in an increase in plaque size and lipid content. We found increased oxidized mtDNA, inflammasome activation, and apoptosis in atherosclerotic lesions and also higher serum IL-1β and IL-18 in Ogg1 −/− Ldlr −/− mice than in Ldlr −/− . Transplantation with Ogg1 −/− bone marrow into Ldlr −/− mice led to larger atherosclerotic lesions and increased IL-1β production. However, transplantation of Ogg1 −/− Nlrp3 −/− bone marrow reversed the Ogg1 −/− phenotype of increased plaque size. Ogg1 −/− macrophages showed increased oxidized mtDNA and had greater amounts of cytosolic mtDNA and cytochrome c, increased apoptosis, and more IL-1β secretion. Finally, we found that proatherogenic miR-33 can directly inhibit human OGG1 expression and indirectly suppress both mouse and human OGG1 via AMP-activated protein kinase. Conclusions: : OGG1 plays a protective role in atherogenesis by preventing excessive inflammasome activation. Our study provides insight into a new target for therapeutic intervention based on a link between oxidative mtDNA damage, OGG1, and atherosclerosis via NLRP3 inflammasome. Abstract : Supplemental Digital Content is available in the text.